Relevansi Kebijakan Penetapan Pidana Kerja Sosial Dalam Sistem Pemidanaan di Indonesia - Gatot Sugiharto (Universitas Ahmad Dahlan, 2016)
Community service order as a kind of sanctions has been applied in some countries for the misdemeanor and violation. In some European countries, a community service order based on the theoretical and practical studies can be an alternative to criminal deprivation of liberty. According to Tongat as stated in his book entitled Pidana Kerja Sosial dalam Pembaharuan Hukum Pidana Indonesia, published Djambatan publisher in 2001, Indonesia is currently reforming the criminal law. He stated that the international tendency becomes significantly valuable and, indeed, has been transformed in the concept of criminal law reform in Indonesia. The conceptual transformation of the referred criminal law can be seen from the adoption of community service order in the new draft of criminal code. This paper examines the relevance of the community service order in the criminal prosecution system in Indonesia that is expected to contribute to ideas in the field of law, especially in the field of criminal law and criminal prosecution system in Indonesia by examining how the new draft of criminal code adopt the community service order as one of the alternative types of sanctions.